Melanocortin 3 receptor gene polymorphism is associated with polycystic ovary syndrome in Turkish population. (3rd August 2019) - Hepsen, Sema; Cakal, Erman; Karakose, Melia; Eyerci, Nilnur; Saat, Hanife; Beysel, Selvihan; Oztekin, Sanem; Pinarli, Ferda; Parlak, Mesut
Abstract: Polycystic ovary syndrome (PCOS) is a frequent complex disorder with an ill-defined etiology. Genetic factors seem rather effective at the occurrence of the disease, however, the evidence of established various studies results are unsatisfied. We aimed to make a contribution to the genetic baseline of the disease by investigating melanocortin 3 receptor gene polymorphism in affected patients. 101 PCOS patients and 162 age-matched healthy volunteered control subjects recruited to the study. PCOS patients classified according to their BMI class and insulin resistance situation. Anthropometric measurements, physical examination results, laboratory findings, and hormone levels were recorded for each participant and analysis of two SNPs on the MC3R gene; rs3746619 and rs3827103 were performed. Although no significant difference was observed in rs3827103 polymorphism between PCOS patients and controls; rs3746619 polymorphism was determined associated with PCOS in the heritage of dominant (AA + AC) and co-dominant (AA) genotypes. Two polymorphisms did not found related to obesity and insulin resistance in PCOS subgroups analysis. MC3R gene rs 3746619 polymorphism was found associated with PCOS in the Turkish population and may make a contribution to the genetic baseline of the disease.